Anesthesia practice in the era of artificial intelligence - Laxmi Pathak, (Journal of Universal College of Medical Sciences, 2026)
Artificial intelligence (AI) is rapidly transforming the anesthetic practice through advanced data analysis, machine learning, deep learning, and natural language processing. In peri-operative care, AI is helpful in addressing patient safety by predicting difficult airway management, adverse events, intraoperative hypotension, hypoxia, and postoperative complications. AI-assisted systems such as Hypotension Prediction Index and Closed Loop Anesthesia Delivery Systems enable real-time monitoring and automated adjustment of anesthetic drugs, ventilation, and hemodynamic support. Despite all these advantages, challenges still remain regarding integrating AI with existing healthcare systems, implementation costs, data quality, ethical accountability, and reliability on technology. Clear regulatory frameworks, clinician supervision, and further large-scale clinical trials are necessary before widespread adoption of AI in anesthetic practice.